International Trade and Tax Evasion in Benin: An Assessment Based on Imports from France and China - Magbonde, Gildas; Fahinde, Charles; Abodohoui, Alexis; Su, Zhan (Journal of Comparative International Management)

(untitled) (Management Futures, 2018)
In this study, we analyzed the drivers of tax evasion occurring through international trade between Benin and its major import partners, namely France - a Western country - and China, a non-Western country. To this end, we scrutinized the co-movement between tax rates and tax evasion, and investigated whether tax evasion in Benin is driven by misclassification behavior or not. Unobservable by nature, tax evasion was measured by missing imports. The results show a positive relationship between tax rates and missing imports expressed in value and in quantity on products from China. Concerning France, the relationship is positive in value but negative in quantity. These two effects combined together result in a weak tax evasion on products imported from France compared to those from China. There is evidence of misclassification only on products imported from France.